Martensitic transformation and magnetic field induced effects in Ni42Co8Mn39Sn11 metamagnetic shape memory alloy - Lazpita, P.; Sasmaz, M.; Cesari, E.; Barandiaran, J. M.; Gutierrez, J.; Chernenko, V. A. (Pergamon-Elsevier Science Ltd, 2016)
Transformation and multifunctional properties of a polycrystalline Ni42Co8Mn39Sn11 metamagnetic shape memory alloy have been investigated by extensive measurements of thermomagnetization, thermal expansion and thermoresistance under magnetic field. The martensitic transformation (MT) at zero field is near 300 K but changes moderately with field. Magnetization loops at room temperature show metamagnetic behavior and complete field-induced MT below 12 T. A non-linear phase diagram 'transformation temperatures versus field' has been established. The correlation between the transformation entropy, Delta S, with magnetic field, and temperature spat between MT and Curie temperature has been also established. A transformation volume effect of about 0.45% has been estimated at MT. It has been experimentally proved that the metamagnetic effect is at the origin of the giant effects of the studied alloy, such as volume magnetostriction and magnetoresistance, which have practical importance. (C) 2016 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Ni(Co)-Mn-Sn metamagnetic shape memory alloy; Martensitic transformation; Giant magnetostriction; Giant magnetoresistance; Transformation entropy; Volume effect